Targeting Macrophage Dysregulation for Viral Infections: Novel Targets for Immunomodulators - Reece, Monica D.; Taylor, Ruby R.; Song, Colin; Gavegnano, Christina (Frontiers in Immunology, 2021)
A major barrier to human immunodeficiency virus (HIV) cure is the latent viral reservoir, which persists despite antiretroviral therapy (ART), including across the non-dividing myeloid reservoir which is found systemically in sanctuary sites across tissues and the central nervous system (CNS). Unlike activated CD4+ T cells that undergo rapid cell death during initial infection (due to rapid viral replication kinetics), viral replication kinetics are delayed in non-dividing myeloid cells, resulting in long-lived survival of infected macrophages and macrophage-like cells. Simultaneously, persistent inflammation in macrophages confers immune dysregulation that is a key driver of co-morbidities including cardiovascular disease (CVD) and neurological deficits in people living with HIV (PLWH). Macrophage activation an d dysregulation is also a key driver of disease progression across other viral infections including SARS-CoV-2, influenza, and chikungunya viruses, underscoring the interplay between macrophages and disease progression, pathogenesis, and comorbidity in the viral infection setting. This review discusses the role of macrophages in persistence and pathogenesis of HIV and related comorbidities, SARS-CoV-2 and other viruses. A special focus is given to novel immunomodulatory targets for key events driving myeloid cell dysregulation and reservoir maintenance across a diverse array of viral infections.